Prevalence of mild serum vitamin B12 deficiency in rural and urban Costa Rican young adults - Holst Schumacher, Ileana (2007)
Objective. Recent studies have shown an increase of mild serum cobalamin (vitamin B12) deficiency in some Latin American countries; however, no data are available from Costa Rica. The purpose of this work was to establish the prevalence of serum vitamin B12 deficiency among Costa Rican young adults and to study some factors that may help explain the serum cobalamin concentrations. Methods. A cross-sectional survey was conducted among 400 adults aged 20 to 40 years old from urban and rural areas of the central valley of Costa Rica to determine serum vitamin B12 levels. Additionally, cobalamin dietary intake and the detection of Helicobacter pylori IgG antibodies were studied as possible determinants of the serum vitamin B12 concentrations. Results. The mean serum concentration of vitamin B12 was 268 ± 125 pmol/L, and no significant differences were found by gender or area. Study data indicate an overall prevalence of inadequate serum cobalamin levels of 42.4% (11.2% deficient and 31.2% marginal); more than 50% but less than 75% of individuals had an intake of vitamin B12 below the U.S. Estimated Average Requirement (EAR) and 61.2% had IgG antibodies to H. pylori. Conclusions. The prevalence of mild serum vitamin B12 deficiency in young Costa Rican subjects is as high as in other Latin American countries. More investigation should be done to elucidate the etiological factors that are generating deficient and marginal serum cobalamin levels in Costa Rican adults in order to define appropriate public health actions.